1992
DOI: 10.2307/3578247
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dose Rate on the Survival of Irradiated Human Skin Fibroblasts

Abstract: The survival of cells in density-inhibited, confluent cultures maintained at 37 degrees C was examined following exposure to 137Cs gamma rays at low dose rates (0.023 or 0.153 Gy/h) or to 60Co gamma rays at a single high dose rate (0.70-0.75 Gy/min). Cells from an ataxia telangiectasia (AT) homozygote showed no dose-rate effect, whereas a three- to fivefold increase in D0 was observed for all other cell strains exposed at low dose rates. The magnitude of the dose-rate effect did not differ significantly among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 8 publications
2
11
0
Order By: Relevance
“…Taken together, these data strongly argue that the increased cell killing (inverse dose rate effects) and reduced ␥-H2AX levels following LDR IR exposures are primarily a consequence of reduced ATM activation. This hypothesis is in accordance with the finding that cells lacking ATM do not show inverse dose rate effects (34).…”
Section: Low Level Dna Damage Results In Reduced Signaling Across a Rsupporting
confidence: 93%
See 1 more Smart Citation
“…Taken together, these data strongly argue that the increased cell killing (inverse dose rate effects) and reduced ␥-H2AX levels following LDR IR exposures are primarily a consequence of reduced ATM activation. This hypothesis is in accordance with the finding that cells lacking ATM do not show inverse dose rate effects (34).…”
Section: Low Level Dna Damage Results In Reduced Signaling Across a Rsupporting
confidence: 93%
“…1 and 4A). This inverse dose rate effect on cell survival has been known to exist for many cell types, although a complete explanation for its cause has been lacking (21,24,(33)(34)(35). A similar inverse dose rate effect is also known to exist in the production of genomic mutations following radiation exposure (6), which may be a consequence of the ineffective activation of repair mechanisms, as shown by the data presented here.…”
Section: Low Level Dna Damage Results In Reduced Signaling Across a Rsupporting
confidence: 51%
“…Radiation dose-rate is an important determinant of biological outcome, with reduced biological effectiveness of radiation exposure at low dose-rate in normal cells. In contrast, ATM null human fibroblast cells are equally sensitive to low and high dose-rate irradiation (Nagasawa et al 1992, Nakamura et al 2006. Whether A-T heterozygotes are also equally sensitive to low and high dose-rate irradiation is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The bystander effect was first reported by Nagasawa et al (1992), who observed chromosome damage in 30% of cells following exposure to a broad field of a-particles such that only 1% of cell nuclei are actually hit. Since then, the bystander effect has become one of the most widely studied of the non-targeted effects, which also include genomic instability, adaptive responses, low-dose hypersensitivity, the inverse dose-rate effect and the regulation of genes at low-doses (Morgan, 2003a(Morgan, , 2003b.…”
Section: Bystander Effectmentioning
confidence: 91%